Estimation of Oil-Water Contact Level Using Different Approaches: A Case Study for an Iraqi Carbonate Reservoir - Al-Rubaye, Wisam I.; Ghanem, Dhiaa S.; Mohammed Kh, Hussein; Abdulzahra, Hayder; Saleem, Ali M.; Abbas, Abbas R. (Journal of Petroleum Research and Studies, 2020)
In petroleum industry, an accurate description and estimation of the Oil-Water Contact (OWC) is very important in quantifying the resources (i.e. original oil in place (OIIP)), and optimizing production techniques, rates and overall management of the reservoir. Thus, OWC accurate estimation is crucial step for optimum reservoir characterization and exploration. This paper presents a comparison of three different methods (i.e. open hole well logging, MDT test and capillary pressure drainage data) to determine the oil water contact of a carbonate reservoir (Main Mishrif) in an Iraqi oil field "BG”. A total of three wells from "BG" oil field were evaluated by using interactive petrophysics software "IP v3.6". The results show that using the well logging interpretations leads to predict OWC depth of -3881 mssl. However, it shows variance in the estimated depth (WELL X; -3939, WELL Y; -3844, WELL Z; -3860) mssl, which is considered as an acceptable variation range due to the fact that OWC height level in reality is not constant and its elevation is usually changed laterally due to the complicated heterogeneity nature of the reservoirs. Furthermore, the results indicate that the MDT test can predict a depth of OWC at -3889 mssl, while the capillary drainage data results in a OWC depth of -3879 mssl. The proper MDT data and SCAL data are necessary to reduce the uncertainty in the estimation process. Accordingly, the best approach for estimating OWC is the combination of MDT and capillary pressure due to the field data obtained are more reliable than open hole well logs with many measurement uncertainties due to the fact of frequent borehole conditions.